Fire behaviour of lightweight concrete units based on corn cob aggregate - Nuno, Alves (2016)
Recent research works have concluded that corn cob may have interesting material properties, in particular, lightness, and thermal and sound insulation abilities. In this research work, corn cob is proposed as an alternative sustainable aggregate for lightweight concrete masonry unit (CMU) manufacturing. The corn cob requires to be granulated previously in order to obtain adequate particle size grade. Subsequently, the particles are wrapped in a cement paste with the purpose of reducing their water abortion and adherent capacities. CMU are current applied in the building of partition walls. The main goal of this research work consists on studying the fire behaviour of partition walls built with CMU of processed corn cob granulate (CMU-PCC).